In silico transcriptional analysis of mRNA and miRNA reveals unique biosignatures that characterizes different types of diabetes - Cubillos-Angulo, Juan Manuel (2020)
Intramural Program of Fundac¸ão Oswaldo Cruz (FIOCRUZ) and by the Brazilian National Council for Scientific and Technological Development (CNPq). K.F.F. received a fellowship from the Programa Nacional de Po´s-Doutorado, Coordenac¸ão de Aperfeic¸oamento de Pessoal de Nı´vel Superior (CAPES) (Finance Code 001). The work of B.B.A. was supported by grants from the NIH (U01AI115940, R01AI069923-08, R01AI20790- 02). BBA and A.T.L.Q are senior investigators from CNPq. J. M. C-A. was supported by the Organization of American States - Partnerships Program for Education and Training (OAS-PAEC) and Coordenac¸ão de Aperfeic¸oamento de Pessoal de Nı´vel Superior (CAPES) (Finance Code 001). C. L.V. is a research fellow from CNPq.